2022
DOI: 10.3389/fmicb.2022.1073350
|View full text |Cite
|
Sign up to set email alerts
|

Tremella fuciformis polysaccharide reduces obesity in high-fat diet-fed mice by modulation of gut microbiota

Abstract: Obesity is a metabolic disease associated with gut microbiota and low-grade chronic inflammation. Tremella fuciformis is a medicinal and edible fungus; polysaccharide (TP) is the main active component, which has a variety of biological activities, such as hypoglycemic and hypolipidemic. However, the anti-obesity effects and potential mechanisms of TP have never been reported. This study was conducted to elucidate the inhibitory effect of TP on high-fat diet (HFD)-induced obesity in mice. Mice were split into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…29,30 Notably, a study showed that norank_f__norank_o__Clostridia_UCG-014 was positively correlated with blood glucose concentration and had increased abundance in animal models of diabetes and obesity. 31 That is consistent with our findings that norank_f__norank_o__Clostridia_UCG-014 was positively correlated with FBG and HbA1c, increasing the concentration of 2-hydroxybutyric acid, but the abundance of that bacterium was the lowest in the MET group. In patients with diabetes who take metformin, changes in the gut microbiota were associated with a substantial decrease in 2-hydroxybutyric acid concentration, an increase in taurine concentration, and a reduction in intestinal glucose absorption.…”
Section: Discussionsupporting
confidence: 91%
“…29,30 Notably, a study showed that norank_f__norank_o__Clostridia_UCG-014 was positively correlated with blood glucose concentration and had increased abundance in animal models of diabetes and obesity. 31 That is consistent with our findings that norank_f__norank_o__Clostridia_UCG-014 was positively correlated with FBG and HbA1c, increasing the concentration of 2-hydroxybutyric acid, but the abundance of that bacterium was the lowest in the MET group. In patients with diabetes who take metformin, changes in the gut microbiota were associated with a substantial decrease in 2-hydroxybutyric acid concentration, an increase in taurine concentration, and a reduction in intestinal glucose absorption.…”
Section: Discussionsupporting
confidence: 91%
“…The gut microbiome consists of thousands of bacterial species, mainly Bacteroidota, Firmicutes, Proteobacteria, and Actinobacteria (Benahmed et al, 2021;Pung et al, 2022). The development of obesity is strongly correlated with gut microbiota, according to several researches (He et al, 2022;Kang et al, 2022;Su et al, 2022). The development of obesity is impacted by how a high-fat diet (HFD) changes the gut microbiota's composition by drastically increasing the ratio of Firmicutes to Bacteroidota (F/B) (Houtman et al, 2022;Indiani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it effectively inhibited weight gain, fat accumulation, and liver weight increase induced by HFD in mice. [ 63 ] Similarly, GLPs maintained gut barrier function, increased the production of SCFAs, and upregulated the expression of GPR43, thereby improving endotoxemia in mice. Consequently, it not only suppressed obesity, hyperlipidemia, inflammation, and fat accumulation induced by the HFD but also restored gut microbiota dysbiosis caused by the HFD.…”
Section: Mechanisms Underlying the Influence Of Polysaccharides On Li...mentioning
confidence: 99%